Silylium-Ion-Initiated Twofold Halodealkylation of Fully Alkylated Silanes - Randt, Tobias; He, Tao; Klare, Hendrik F. T.; Oestreich, Martin (Synthesis, 2024)
The synthesis of silanes starting from multifunctionalized precursors often suffers from low chemoselectivity due to the similar kinetic reaction profiles, leading to the formation of difficult to separate side products. The opposite approach, which is an access based on unreactive tetraalkylsilanes as starting materials, is far less developed. Making use of the silylium-ion-initiated chemoselective halodealkylation of tetraalkylsilanes recently developed by our laboratory, an extension of this protocol, namely the direct synthesis of dihalosilanes from tetraalkylsilanes, is reported. Following a sequence of halodehydrogenation and halodealkylation, trialkylhydrosilanes can also be converted into dihalosilanes. Commercially available 1,2-dihaloethane acts as the halogen source and is involved in the generation of the catalytically active arenium ion by an SEAr substitution of the benzene solvent. The formation of an uncommon halogen-substituted silylium ion as an intermediate is assumed, likely accounting for the need of an elevated reaction temperature.
Keywords: arenium ions; halodealkylation; halodehydrogenation; Lewis acids; silicon; silylium ions